Nestanak Heroja . The Disappearance of Heroes - Mandic, Ivan (Akademski Filmski Centar, 2009)
Verzio FF Submission Following the war and the political changes in Serbia, many street names in Belgrade, named after famous people and historical events of World War II, have been changed. This film follows the work of the Street and Squares Commission, appointed by the city of Belgrade, as well as reactions of individuals and groups on the imposed changes.